The American Christian Palestine Committee, the Holocaust, and Mainstream Protestant Zionism, 1938–1948 - Carenen, Caitlin (Holocaust and genocide studies, 2010)
Scholarship has long assumed that American Christian support for Zionism during the Holocaust was limited and that Christians were generally indifferent to the Jewish plight. A new look, however, suggests that the Holocaust catalyzed mainstream American Protestant support for establishing a Jewish state. Archival sources permit the author of this study to trace the emergence of the politically influential American Christian Palestine Committee and its efforts on behalf of the Zionist cause. Despite hostility within some circles, widespread knowledge of the Holocaust and the activities of the ACPC persuaded many Protestant leaders to support the establishment of Israel, fundamentally changing Protestant-Jewish relations after 1948.